A COURSE OF LECTURES ON ECOLOGY AND LIFE SAFETY BASICS - Bobrenko, M.A. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The textbook is recommended for organization of the educational process in conducting lectures on the course "Ecology and life safety basics". The textbook is intended for students, and can also be useful for a wide range of teachers, educators and specialists in other areas interested in the basics of ecology and life safety.